2013
DOI: 10.1021/bi400801q
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Protein–RNA Complexes Involving a RNA Recognition Motif Engineered To Bind Hairpins with Seven- and Eight-Nucleotide Loops

Abstract: U1A binds U1hpII, a hairpin RNA with a 10-nucleotide loop. A U1A mutant (ΔK50ΔM51) binds U1hpII-derived hairpins with shorter loops, making it an interesting scaffold for engineering or evolving proteins that bind similarly sized disease-related hairpin RNAs. However, a more detailed understanding of complexes involving ΔK50ΔM51 is likely a prerequisite to generating such proteins. Toward this end, we measured mutational effects for complexes involving U1A ΔK50ΔM51 and U1hpII-derived hairpin RNAs with seven- o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Based on previous studies(38), including our own(39), we hypothesized that high-throughput screening would yield a privileged β2-β3 loop which selectively recognizes TAR RNA. Based on this hypothesis, we hypothesized that high-throughput screening would yield a privileged β2-β3 loop that is selective for TAR RNA recognition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous studies(38), including our own(39), we hypothesized that high-throughput screening would yield a privileged β2-β3 loop which selectively recognizes TAR RNA. Based on this hypothesis, we hypothesized that high-throughput screening would yield a privileged β2-β3 loop that is selective for TAR RNA recognition.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed how mutating the N-terminal U1A RRM (U1A, Figure 1A) alters its target RNA sequence selectivity. (39, 43) In particular, we probed how one or two mutations to putative RNA-binding residues within the β1-α1 and β2-β3 loops lower affinity for U1hpII and increase affinity for Trans-Activation Reporter (TAR) element RNA(44) (Figure 1D). TAR RNA has an extended stem-loop structure that is crucial for efficient transcription of the integrated HIV genome, and is an established therapeutic target.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such adenine-adenine stacks are also of relevance for the oxidation of oligonucleotides [50]. Combinations of p-p interactions also occur in recognition reactions, e.g., between the tyrosine or phenylalanine residues of a protein and the cytosine or adenine moieties of an RNA, respectively [51]. Stack formation between an indole residue (red) of a proteintryptophan and guanine-RNA moieties (blue) in the SR-like protein ZRANB2 and the RNA in its single-stranded RNA-binding domain [52].…”
Section: Entry 3 Inmentioning
confidence: 99%
“…Mutagenesis of residues within putative RNA recognition regions of U1A generally does not result in protein instability and unfolding. (32, 41-43, 46) In addition, certain mutations within the putative RNA-binding regions can lead to altered RNA binding selectivity. For example, researchers have shown that mutating residues within the b2-b3 loop lead to U1A-derived proteins with improved affinity for U1hpII.…”
Section: Introductionmentioning
confidence: 99%